Adverse Perinatal and Maternal Outcomes and Associated Factors among Women with Antepartum Hemorrhage in Jimma University Medical Center, Southwest Ethiopia, 2020 - Melkamu Gelan; Tariku Bekela; Kebanesa Angasu; Mosisa Ebisa (Obstetrics and Gynecology International)
Background. Globally, antepartum hemorrhage is the main cause of perinatal and maternal morbidity and mortality during pregnancy and childbearing. Objective. To assess adverse perinatal and maternal outcomes and associated factors among women with antepartum hemorrhage in Jimma University Medical Center, Southwest Ethiopia, 2020. Methods. Prospective cross-section study was conducted, and data were collected through face to face interview among pregnant women admitted with antepartum hemorrhage. Patient condition was observed and followed up, and patient card was reviewed. Data were coded, checked, entered into EPI version 4.6, and exported to SPSS version 26.0 for analysis. Multivariate logistic regression analysis was made to determine independent factors associated with adverse outcomes. Result. A total of 377 pregnant women were included, and nearly half (192 (50.9%)) of women experienced adverse maternal outcome and 113 (30%) women experienced adverse perinatal outcome. The status of vital sign, address, parity, antenatal care, duration of bleeding before arrival, gestational age, prematurity, and amount of vaginal bleeding were factors significantly associated with adverse maternal and perinatal outcome at p value <0.05. Conclusion. Vital sign derangement, vaginal bleeding for ≥12 hrs, gestation age before 37 weeks, rural address, prim parity, amount of vaginal bleeding, and prematurity baby has predicted high rate of adverse perinatal and maternal outcomes. Recommendation. Jimma Hospital should give patient-centered service and strengthen counseling on danger sign of pregnancy to alert women early health care seeking and immediate resuscitation, and appropriate management should be given for women admitted with APH to minimize of adverse perinatal and maternal outcomes.